Preparation and characterization of a new Schiff base and its metal complexes derived from mebendazole with 3-aminophenols and studying their biological activity. (Journal of the College of Basic Education, 2022)
This work involves the preparation of the ligand [HL1] :-{6-] 1H-benzo-2yl}-Carbamic acid methyl ester [1H-Benzoimidazol-2-ylimino)-phenyl-methyl} from the reaction (Mebendazole) with(3-Aminophenol) under reflux (6 hours) using (THF) as a solvent to predict ligand foregoing . The prepared ligand was characterized using (FT-IR), (UV-Vis), (1H,13C–NMR) spectroscopy and measuring the melting point, Complexes for the above ligand [HL1] with some metal (II) of (Co , Ni , Cu and Zn) metals were prepared. All prepared complexes were characterized by spectrophotometric methods such as (FT-IR) , (UV-Vis) and Atomic Absorption in addition chloride content ,melting point, Magnetic Susceptibility and molar conductivity were also done. All prepared complexes were found to have octahedral geometry. Biological activity for the ligand and some of its complexes was studied against two species of characterized bacteria. " Proteus " and Staphylococcus aureus" " and found from study that complexes [(Co)(L1)2(H2O)2] have more inhibition from the ligand.